EEG Evidence of Altered Functional Connectivity and Microstate in Children Orphaned by HIV/AIDS - Gu, Huang; Shan, Xueke; He, Hui; Zhao, Junfeng; Li, Xiaoming (Frontiers in Psychiatry, 2022)
Children orphaned by HIV/AIDS (‘AIDS orphans’) suffer numerous early life adverse events which have long-lasting effect on brain function. Although previous studies found altered EEG oscillation during resting state in children orphaned by HIV/AIDS, data are limited regarding the alterations in connectivity and microstate. Here, the current study aimed to investigate the functional connectivity (FC) and microstate in children orphaned by HIV/AIDS with resting-state EEG data. Data were recorded from 63 children orphaned by HIV/AIDS and 65 non-orphan controls during close-eyes resting-state. The differences of phase-locking value (PLV) of global average FC and temporal dynamics of microstate were compared between groups. For functional connectivity, children orphaned by HIV/AIDS showed decreased connectivity in alpha, beta, theta and delta band compared to non-orphan controls. For microstate, EEG result demonstrated that children orphaned by HIV/AIDS show increased duration and coverage of microstate C, decreased occurrence and coverage of microstate B and decreased occurrence of microstate D than non-orphan controls. These findings suggest that the microstate and functional connectivity has altered in children orphaned by HIV/AIDS compared to non-orphan controls and provide further evidence that early life stress would alter the structure and function of brain and increase the risk of psychiatric disorders.